The significance of metagenomic next-generation sequencing and targeted next-generation sequencing in the diagnostic evaluation of patients with suspected pulmonary infections - Tang, Yucong; Tang, Shujin; Zhang, Yingchao; Lin, Zhentao; Shan, Shuxiang (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveTo investigate the diagnostic value of metagenomic next-generation sequencing (mNGS) and targeted next-generation sequencing (tNGS) in identifying pathogens in patients with pulmonary infections.MethodsA retrospective analysis was conducted on 155 patients with suspected lung infections who underwent alveolar lavage and were admitted to the Department of Respiratory and Critical Care Medicine at Baodi Hospital, Tianjin Medical University, from July 2023 to December 2023. The bronchoalveolar lavage fluid (BALF) samples obtained were subjected to mNGS, tNGS and culture methods to compare their diagnostic efficacy in identifying lung infection pathogens.ResultsThe results indicated that both tNGS and mNGS methods exhibit comparable detection efficiencies in identifying pathogens in patients with pulmonary infections, significantly outperforming BALF culture approach. In terms of diagnostic accuracy, tNGS exhibited a higher sensitivity than mNGS, with rates of 96.1% and 75.7% respectively (P>0.05). However, the specificity of tNGS was slightly lower than that of mNGS, with rates of 59.1% and 68.2% respectively (P>0.05). It is noteworthy that this difference in specificity was not statistically significant.ConclusiontNGS exhibits a diagnostic efficacy comparable to mNGS, particularly in its sensitivity for identifying lung infections, as evidenced by expert insights and clinical applications. Furthermore, tNGS offers advantages in convenience, time efficiency, and cost-effectiveness, hinting at its potential to serve as an alternative to mNGS in clinical settings.